2010
DOI: 10.1038/nature09634
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression divergence recapitulates the developmental hourglass model

Abstract: The observation that animal morphology tends to be conserved during the embryonic phylotypic period (a period of maximal similarity between the species within each animal phylum) led to the proposition that embryogenesis diverges more extensively early and late than in the middle, known as the hourglass model. This pattern of conservation is thought to reflect a major constraint on the evolution of animal body plans. Despite a wealth of morphological data confirming that there is often remarkable divergence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
418
5
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(468 citation statements)
references
References 44 publications
43
418
5
2
Order By: Relevance
“…We found that the phylogenetic signals were low for many genes (Figure S3d; median values: λ = 0.03, K  = 0.41), suggesting most of the variations observed were not fully accounted for by the BM model. In addition, when we compared the goodness of fit of individual gene expression under BM model against OU models with up to three optima (Butler & King, 2004; Kalinka et al., 2010), we found over 85% of the genes fitted better with one of the OU models than with the BM model (Figure S3e,f), similar to the percentage previously observed (Kalinka et al., 2010). Together, these data suggest that stabilizing selection likely plays an important role in influencing the gene expression patterns in Drosophila .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We found that the phylogenetic signals were low for many genes (Figure S3d; median values: λ = 0.03, K  = 0.41), suggesting most of the variations observed were not fully accounted for by the BM model. In addition, when we compared the goodness of fit of individual gene expression under BM model against OU models with up to three optima (Butler & King, 2004; Kalinka et al., 2010), we found over 85% of the genes fitted better with one of the OU models than with the BM model (Figure S3e,f), similar to the percentage previously observed (Kalinka et al., 2010). Together, these data suggest that stabilizing selection likely plays an important role in influencing the gene expression patterns in Drosophila .…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, previous studies based on genomes and transcriptomes observed that a large fraction of the genes in Drosophila were likely subjected to stabilizing selection (Bedford & Hartl, 2009; Clark et al., 2007; Kalinka et al., 2010; Rifkin, Kim & White, 2003), such that the increase in gene expression divergence eventually reaches a plateau (Bedford & Hartl, 2009) and may be better described by Ornstein‐Uhlenbeck (OU) process (Butler & King, 2004; Martins & Hansen, 1997). …”
Section: Resultsmentioning
confidence: 99%
“…Genes for which we observe no change in H3K27me3 signal may instead be highly diverged at other developmental times. Furthermore, it is possible that the dynamics of histone modification evolution differ depending on the stage of development (Kalinka et al 2010). Additionally, we believe the observed differences in H3K27me3 reflect a lower bound estimate of the possible differences between species.…”
Section: H3k27me3 Conservation Bypassed By Gene Duplicationmentioning
confidence: 83%
“…Indeed, TFs play a crucial role in multicellular eukaryotes. For example, TFs are the master regulators of embryonic development in embryophytes and metazoans (9), and analyses of their embryonic transcriptional profiles support the presence of a phylotypic stage in both lineages (10)(11)(12)(13)(14). These studies have also shown that evolutionarily younger genes tend to be expressed at earlier and later stages of development, whereas the transcriptomes of the middle stages (the phylotypic stage) are dominated by ancient genes (10,13).…”
mentioning
confidence: 88%